Digital Marketing in Enhancing the Commercial Value of Natural Frond Crafts - Oterlo Seropi (Akademi Sertifikasi Profesi Internasional, 2023)
The study aims to promote products made by artisans who use natural fibers within the community. The analysis of the business canvas model revealed that the primary challenge encountered by craftspeople was the difficulty in establishing direct access to consumers. Consequently, artists receive diverse training to effectively market products and reach consumers by utilizing digital marketing via social media platforms (Facebook and Instagram) and business website development. The training empowers them to market handcrafted products to both local and national clients. Through digital marketing, they can extend their reach to promote their products internationally